Erosion and Flooding Risks in the Marly Basins of the Eastern Prerif Mountains (Morocco): A Response to Exceptional Climate Events or to Anthropogenic Pressure - Tribak, Abdellatif (Revista de Estudios Andaluces, 2020)
The Eastern Rif Mountains are frequently subject to exceptional rainfall events, whose consequences are sometimes disastrous. The impact of these phenomena on environments is more important as the majorities of slopes are bare and subject to strong human influence. The protective natural forests of the slopes are almost destroyed; they currently cover only a few peaks of mountains in the region. They represent 1.84% of the total area of wadi Tleta sub-basin and only 1.32% of the Tarmast wadi sub-basin. However, croplands, occupying respectively 60% and 34% in the two sub-basins, extend even on the steepest slopes. Similarly, the accelerated and uncontrolled human occupation of the urban peripheries, located downstream of the basins, amplifies the vulnerability of these environments to the hydrological hazards, that threaten several sites surrounding the agglomeration of Taza. Thus, the whole region is subject to different degradation processes. Hydric erosion affects the majority of the slopes; it causes excessive sediment production that may exceed 60 t ha-1 year-1 in some sub-basins. Similarly, flood disasters are quite common in the region. The flood of 20/9/2000 is a reference, with a volume estimated at 4 million m3(DRH-Sebou 2000). Human and material damage was enormous in the rural centers and in the northern outlying districts of Taza. This contribution aims to present and analyze the combined impacts of the extreme rains and the actions of the human societies on the dynamics of the prerifain environment and its adjoining spaces.